National pilgrimages, pilgrim trains and identity-building - Barna Gábor (Religion, culture, society, 2015)
The spread of public transport in the mid-19th century changed peo-ple’s travel habits. It also brought change in travel for religious purposes, ena-bling a new form of religious mass tourism to emerge. As the railways grew into a European network, distant shrines (as Lourdes, Rome) became more accessible. Long-distance pilgrimages were revived and grew to a mass scale, reviving or augmenting the popularity of some shrines. Special trains were organised for pil-grimages within individual countries too, enabling new trends to flourish. Ethno-logical research and anthropology of religion have paid little attention to this form of mass pilgrimage that is still alive and has ‘traditional’ forms in many countries of Europe. The paper analyses the organisation and itineraries of pilgrim trains and their influence on the shrines, as well as the spread of devotional forms, iden-tity-building both within Hungary and internationally. It analyses mainly reports on travel to Lourdes and Rome at the turn of the 19th to 20th centuries, touches on the “Hungarian holy years” in the 1930s, and the organisation of pilgrim trains following the change of political system (1989-1990).